SOBRE LA HISTOPATOLOGIA DE LA CISTICERCOSIS CEREBRAL - NIETO, DIONISIO (Instituto de Salubridad Publica, CD MEXICO, DF, MEX, 1945)
Methods are described for producing convulsive responses in animals by the use of stimulating drugs or electrical stimuli of faradic or alternating current
BOL INST ESTUD MED BIOL
Keywords: HISTOPATOLOGIA, CISTICERCOSIS CEREBRAL; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL